(untitled) (The International Journal for Scientific Research, 2024)
Background: The heal had distinctive anatomical feature that serve as weight bearing structure and any defect in heal result in gait instability and therefore the tissue used to reconstruct the heel area must be resistant, innervated, and adapted to adjust to the body weight. The aim of study is to evaluate the outcomes of heel reconstruction using the Sensate medial plantar flap in group of patients, emphasizing its efficacy in restoring function and sensation. Patients and Methods: The study is prospective-descriptive case series conducted from 2020-2024, in four hospitals, patients who presented with heel soft tissue defects of various etiologies. SMPF is used in reconstructive. Results: The study involved 26 patients, majority of them being male (92.3%) and the remaining (7.7%) were female, with participants’ mean age was (35.42) years, most of patients present with size defect >3cm in (76.9%), with non-neurotrophic ulcer in (73.1%), preoperative doppler US is used in (69.2%). The overall survival rate of flap (96.15%) and with complication rate (19.15%), (11.5%) necessitate reoperation, these uneventfully complications like total flap loss (3.8%) which reoperated and, partial flap necrosis (3.8%). Donor site covered with split thickness skin graft, with complications such as graft loss / dehiscence which healed with secondary intention (7.7%), (3.8%) total graft loss require reoperation. Conclusion: the use of SMPF for reconstructing heel defect is highly adaptable technique and is widely regarded as one of the best options for repairing soft tissue defect of heel. This is due to its sensitivity and ability to replace the damaged area with similar structure following the idea of “like with like”.